Given that x y z = 1 where x , y , z are positive real numbers and that x + z 1 = 5 , y + x 1 = 2 9 and z + y 1 = n m , where m and n are coprime positive integers. Compute m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
By rearranging the equations we get:
x + x y = x ( y + 1 ) = 5
y + y z = y ( z + 1 ) = 2 9
z + z x = z ( x + 1 ) = n m
Multiplying the equations:
x y z ( x + 1 ) ( y + 1 ) ( z + 1 ) = ( 5 ) ( 2 9 ) ( n m )
Expanding:
x y z ( x y z + x y + x z + y z + x + y + z + 1 ) = ( 5 ) ( 2 9 ) ( n m ) = 1 4 5 ( n m )
Substitute x y z = 1 as well as x y = z 1 , x z = y 1 , y z = x 1 :
1 ( 1 + ( x + z 1 ) + ( y + x 1 ) + ( z + y 1 ) + 1 ) = 1 4 5 ( n m )
1 + 5 + 2 9 + n m + 1 = 1 4 5 ( n m )
Solving for n m yields n m = 4 1 . So 1 + 4 = 5
⎩ ⎪ ⎨ ⎪ ⎧ x + z 1 = 5 y + x 1 = 2 9 . . . ( 1 ) . . . ( 2 )
( 1 ) × y z : x y z + z y z 1 + y y 1 + 1 y 1 z + y 1 = 5 y z = 5 y z = 5 z = 5 z − 1 = 6 z − 1 Divide both sides by y . Both sides add z . . . . ( 3 )
( 2 ) × y z 1 : y z y + x y z 1 z 1 + 1 z 1 + z 1 + z 1 + 3 0 z = y z 2 9 = y z 2 9 = y z 2 9 = y 2 9 = 2 9 ( z + y 1 ) Both sides add 2 9 z . . . . ( 4 )
We note that 2 9 ( 3 ) = ( 4 ) :
⟹ 2 9 ( 6 z − 1 ) 1 7 4 z − 2 9 1 4 4 z ⟹ z ( 3 ) : z + y 1 = 1 + 3 0 z = 1 + 3 0 z = 3 0 = 2 4 5 = 6 z − 1 = 6 × 2 4 5 − 1 = 4 1
⟹ m + n = 1 + 4 = 5
First of all, in the first equation,
⟹ ⟹ ⟹ ⟹ x + z 1 = 5 z z x + 1 = 5 x y 1 y 1 + 1 = 5 ( 1 + y ) x = 5 x = 1 + y 5
Substituting x with this expression in the next equation, we obtain
⟹ ⟹ y + x 1 = 2 9 y + 5 1 + y = 2 9 y = 2 4
So,
x = 1 + y 5 = 2 5 5 = 5 1
And,
⟹ ⟹ ⟹ x + z 1 = 5 5 1 + z 1 = 5 z 1 = 5 2 4 z = 2 4 5
Finally,
z + x 1 = 2 4 5 + 2 4 1 = 2 4 6 = 4 1 = n m
Thus, m + n = 1 + 4 = 5
Multiplying the equations, we get
( x + z 1 ) ( y + x 1 ) ( z + y 1 ) =
x y z + x + y + z + x 1 + y 1 + z 1 + x y z 1 =
1 + x + y + z + x y z x y + y z + x z + 1 =
x + y + z + x y + y z + x z + 2 =
2 5 ⋅ 5 ⋅ n m
Adding the equations, we get:
( x + z 1 ) + ( y + x 1 ) + ( z + y 1 ) =
x + y + z + x y z x y + y z + x z =
x + y + z + x y + y z + x z =
2 9 + 5 + n m
Letting x + y + z + x y + x z + y z = a , we get:
a + 2 = 1 4 5 n m
a = 3 4 + n m
Subtracting the equations,
2 = 1 4 4 n m − 3 4
1 4 4 n m = 3 6
n m = 4 1
m + n = 1 + 4 = 5
Did the same way
Note the following identity.
( x + z 1 ) ( y + x 1 ) ( z + y 1 ) − ( x + z 1 ) − ( y + x 1 ) − ( z + y 1 ) = x y z + x y z 1
Thus if z + y 1 = A then ( 5 ) ( 2 9 ) A − 5 − 2 9 − A = 2 . Solving, A = 4 1 and the answer is 1 + 4 = 5 .
By multiplying the first two "reciprocal-summation" identities: ( x + z 1 = 5 ) × ( y + x 1 = 2 9 )
Gives y ( x + z 1 ) + 1 + x z 1 = 1 4 5
But, we know that x y z = 1 , i.e., x z 1 = y , and x + z 1 = 5 .
Therefore, by substituting in the above expression, we conclude that 6 y = 1 4 4 or y = 2 4 and, by the previous identities: x = 5 1 ; and z = 2 4 5 .
Hence, z + y 1 = 2 4 5 + 2 4 1 = 4 1 .
So, m + n = 1 + 4 = 5 .
First we need to substitute the value of x in terms of y and z and then substitute the value of x and the find the answer
Problem Loading...
Note Loading...
Set Loading...
I don't know is there an easier method to find z + y 1 , but this below is my method x + z 1 x z + 1 1 x y z ∴ y = 5 = 5 z = z ( 5 − x ) = z ( 5 − x ) = x 5 − 1
Putting it into the third equation gives us x 5 − 1 + x 1 = 2 9 x 6 = 3 0 ∴ x = 5 1
Substitute x into all equations gives us y = 2 4 , z = 2 4 5
Hence, z + y 1 = 2 4 5 + 2 4 1 = 4 1
So m + n = 1 + 4 = 5